Resin film, laminate, and package
By using a composite material of polyethylene terephthalate resin film and a gas barrier layer, the problem of degradation of gas barrier performance caused by external forces during transportation of the packaging material is solved, and the material stability and gas barrier effect under the action of external forces are achieved.
Patent Information
- Application Number
- JP2024203158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During transportation, existing packaging materials can easily lead to a degradation of gas barrier properties due to external forces, and cannot effectively resist damage caused by external forces such as folding or twisting.
A composite material including a resin film containing polyethylene terephthalate and a gas barrier layer is used. The resin film has appropriate softness and hardness, which can reduce plastic deformation under the action of external forces and maintain the integrity of the gas barrier layer.
It effectively suppresses the decline in gas barrier performance, ensures that the packaging materials are not easily damaged during transportation, and maintains the gas barrier effect.
Smart Images

Figure 2025015840000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film, a laminate including the resin film, and a packaging material. [Background technology]
[0002] Resin films containing polyethylene terephthalate are widely used as packaging materials for packaging objects such as food, medicines, and cosmetics. In order to prevent deterioration in the quality of the objects, it is preferable that the packaging material has gas barrier properties that make it difficult for gases such as oxygen and water vapor to pass through. For this reason, a laminate of a transparent film and a barrier layer containing a metal film or a metal oxide film is used as the packaging material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-81607 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventionally, the gas barrier properties of packages have been evaluated assuming the time of manufacture, storage, and even use. However, during the distribution process of a packaged product, an external force that causes deformation such as folding or twisting of the packaging material may be repeatedly applied to the product, such as when the product is subjected to vibration during transportation, and there is a demand for a packaging material that can suppress a decrease in gas barrier properties even when such an external force is applied.
[0005] The present invention aims to provide a resin film, a laminate, and a package that can suppress deterioration of the gas barrier properties of a laminate against external forces applied to the laminate, particularly against external forces applied to the laminate during transportation. [Means for solving the problem]
[0006] The resin film for solving the above problem is a resin film containing polyethylene terephthalate, which is used to produce a packaging body from a laminate having the resin film and a gas barrier layer, and has a yield stress in the machine direction of the resin film according to JIS K7161-1:2014 of 109 MPa or more and 117 MPa or less.
[0007] The laminate for solving the above problem includes the above resin film and a gas barrier layer. The packaging material for solving the above problem includes the above resin film and a gas barrier layer.
[0008] According to each of the above configurations, the resin film has a softness that is not too brittle and a hardness that is not likely to cause excessive plastic deformation. By using this resin film in a laminate for forming a package, it is possible to suppress the occurrence of defects in the bond between the resin film and the gas barrier layer or in the gas barrier layer itself due to external forces caused by repeated vibrations during transportation, etc., and ultimately the deterioration of the gas barrier properties of the laminate due to defects.
[0009] In the resin film, in a stress-strain curve obtained in the machine direction, the slope of the stress-strain curve after yielding and in a range of strain of 0.2 or more and 0.4 or less may be 75 or more and 117 or less.
[0010] According to the above-mentioned configuration, when a stress greater than or equal to the stress causing plastic deformation is applied to the resin film, the strain at the breaking point is prevented from becoming small, thereby preventing the resin film from breaking and, in turn, preventing defects from occurring in the gas barrier layer formed on the resin film.
[0011] The resin film may have a breaking strength in the machine direction of 153 MPa or more and 183 MPa or less. This configuration prevents either the stress or the strain that the resin film can withstand without breaking from becoming excessively low, thereby making it difficult for the resin film to break. As a result, it is possible to prevent defects in the deposition layer caused by breakage of the resin film 10.
[0012] In the laminate, the gas barrier layer may include a vapor deposition layer and a coating film, and the vapor deposition layer may be formed of at least one of aluminum oxide and silicon oxide. In the laminate, the vapor deposition layer and the coating film may be in contact with each other.
[0013] In the above laminate, the coating film is Si(OR 1 ) 4 , or R 2 Si(OR 3 ) 3 (OR 1 and OR 3 is a hydrolyzable group, R 2 is an organic functional group) or one or more hydrolyzates of a silicon compound, and a water-soluble polymer having a hydroxyl group. Effect of the Invention
[0014] According to the present invention, it is possible to suppress the deterioration of the gas barrier properties of the laminate. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a cross-sectional view showing a structure of a resin film according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a structure of a laminate according to one embodiment. [Diagram 3] FIG. 2 is a perspective view showing a structure of a packaging body in one embodiment. [Figure 4] An example of a stress-strain curve obtained for a resin film. [Diagram 5] Stress-strain curves of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of a resin film, a laminate, and a package will be described with reference to Figures 1 to 5. Below, the resin film, the laminate, the package, the physical properties of the resin film, and examples will be described in order.
[0017] [Resin film] The resin film 10 will be described with reference to FIG. The material constituting the resin film 10 shown in Fig. 1 includes polyethylene terephthalate (PET). The PET is at least one of virgin PET newly synthesized from raw materials such as petroleum, and recycled PET, which is regenerated PET. PET products that are subject to recycling include used PET bottles. The recycled PET constituting the resin film 10 is at least one of PET regenerated by mechanical recycling and PET regenerated by chemical recycling.
[0018] Mechanical recycling is achieved by crushing and washing PET products to remove surface dirt and foreign matter, and then exposing the resin to high temperatures to remove contaminants remaining inside the resin. Chemical recycling is achieved by crushing and washing PET products to remove surface dirt and foreign matter, and then depolymerizing the resin to return it to an intermediate raw material, which is then refined and repolymerized. Mechanical recycling does not require large-scale facilities for chemical reactions, so the cost and environmental impact required for producing recycled PET are lower than those of chemical recycling. To reduce the cost and environmental impact, the recycled PET contained in the resin film 10 is preferably PET regenerated by mechanical recycling.
[0019] In addition to recycled PET, the resin film 10 may contain virgin PET, which is PET newly synthesized from raw materials such as petroleum. In order to reduce costs and environmental impact, the proportion of recycled PET to the total mass of the resin film 10 is preferably 60% or more and 100% or less.
[0020] The repeating units constituting PET include diol units and dicarboxylic acid units. In virgin PET, an example of the diol unit is ethylene glycol, and an example of the dicarboxylic acid unit is terephthalic acid. In recycled PET, an example of the diol unit is ethylene glycol, and an example of the dicarboxylic acid unit includes terephthalic acid and isophthalic acid. From the viewpoint of easily obtaining a yield stress of 109 MPa or more and 117 MPa or less of the resin film, it is preferable that the ratio of isophthalic acid to all dicarboxylic acid units is 0.5 mol % or more and 5 mol % or less. It is possible for the diol unit to contain diethylene glycol.
[0021] In the PET used for recycling, the diol unit is ethylene glycol and the dicarboxylic acid unit contains terephthalic acid and isophthalic acid in order to suppress crystallization of the PET and improve the workability of the material. The dicarboxylic acid unit of the recycled PET that constitutes the resin film 10 contains the dicarboxylic acid unit of such a PET bottle, i.e., terephthalic acid and isophthalic acid.
[0022] The average molecular weight of the PET contained in the resin film 10 is preferably 1000 or more and 1 million or less. The resin film 10 may contain a resin other than PET and various additives. The additives may be, for example, a plasticizer.
[0023] The resin film 10 is composed of a single layer or multiple layers. When the resin film 10 is composed of multiple layers, the materials constituting each layer may be the same or different. An example of a configuration in which the materials constituting each layer are different from each other is a laminate of a layer formed from recycled PET and a layer formed from virgin PET. Another example of a configuration in which the materials constituting each layer are different from each other is a laminate of a layer containing recycled PET at a first ratio to virgin PET and a layer containing recycled PET at a second ratio to virgin PET that is different from the first ratio.
[0024] The thickness of the resin film 10 is selected according to various properties required for the package, such as various environmental resistances such as heat and moisture, storage stability of the contents, filling stability of the contents, sealing processability, printing resistance including marking, etc. From the viewpoint of improving the processability of the resin film 10, for example, the thickness of the resin film 10 is preferably selected from the range of 3 μm to 100 μm, and more preferably selected from the range of 6 μm to 50 μm.
[0025] The method for forming the resin film 10 is a melt extrusion method or a melt coextrusion method. The flow direction of the resin film 10 is the direction in which PET molding progresses during the production of the resin film 10. The flow direction is also called the MD (Machine Direction) direction or the longitudinal direction. The direction perpendicular to the flow direction is also called the TD (Transverse Direction) direction or the lateral direction. When the resin film 10 is composed of multiple layers, the flow direction of each layer is the same.
[0026] The resin film 10 is a non-stretched film, a uniaxially stretched film stretched at a predetermined ratio in the MD or TD, or a biaxially stretched film stretched at a predetermined ratio in the MD and TD sequentially or simultaneously. When the resin film 10 is composed of multiple layers, the stretching direction of each layer is the same.
[0027] [Laminate] The laminate 20 will be described with reference to Fig. 2. The laminate 20 includes a resin film 10 and a gas barrier layer 11. The gas barrier layer 11 has a function of enhancing the gas barrier properties of the laminate 20.
[0028] The gas barrier layer 11 includes, for example, a vapor-deposited film. The vapor-deposited film is an inorganic oxide film or a metal film. The inorganic substance included in the inorganic oxide may be, for example, an oxide of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, yttrium, or the like. The metal may be, for example, aluminum, magnesium, tin, sodium, titanium, lead, zirconium, yttrium, gold, chromium, or the like.
[0029] The method for forming the vapor-phase deposition film may be, for example, a vacuum deposition method, a sputtering method, an ion plating method, or a plasma vapor deposition method (CVD). From the viewpoint of increasing the productivity of the laminate, the method for forming the vapor-phase deposition film is preferably a vacuum deposition method. In the vacuum deposition method, it is preferable to use any one of an electron beam heating method, a resistance heating method, and an induction heating method as a method for heating the deposition material. From the viewpoint of increasing the degree of freedom in the selection of the deposition material, it is preferable to use an electron beam heating method. From the viewpoint of increasing the adhesion between the vapor-phase deposition film and the resin film 10 and from the viewpoint of increasing the density of the vapor-phase deposition film, it is possible to use a plasma assist method and an ion beam assist method in the vacuum deposition method. From the viewpoint of increasing the transparency of the deposition layer, the gas barrier layer 11 may be formed by a reactive deposition method. In the reactive deposition method, a reactive gas such as oxygen gas is supplied to the film formation space.
[0030] The laminate 20 for forming a transparent packaging bag comprises a vapor-phase deposited film formed from an inorganic oxide. In particular, vapor-phase deposited films formed from aluminum oxide and silicon oxide are preferred. The laminate 20 for forming a light-shielding packaging bag comprises a vapor-phase deposited film formed from a metal. In particular, a vapor-phase deposited film formed from aluminum is preferred.
[0031] The gas barrier layer 11 may be formed of a plurality of barrier layers. In this case, each barrier layer may be formed of the same material, or the plurality of barrier layers may include a barrier layer formed of a first material and a barrier layer formed of a second material different from the first material.
[0032] The thickness of the gas barrier layer 11 is selected, for example, from the range of 5 nm to 300 nm. When the thickness of the gas barrier layer 11 is 5 nm or more, the uniformity of the gas barrier layer 11 can be increased and the gas barrier layer 11 can have a sufficient thickness. Therefore, the gas barrier layer 11 can fully exhibit the gas barrier function. On the other hand, when the thickness is 300 nm or less, the gas barrier layer 11 can maintain flexibility. This suppresses cracks in the gas barrier layer 11 caused by external factors such as bending and pulling after film formation. The thickness of the gas barrier layer 11 is appropriately selected according to the type of inorganic compound forming the gas barrier layer 11 and the configuration of the laminate 20. From the viewpoint of increasing the uniformity in the thickness of the gas barrier layer 11, the thickness of the gas barrier layer 11 is more preferably included in the range of 10 nm to 150 nm.
[0033] The gas barrier layer 11 may include a coating film having gas barrier properties in addition to or instead of the above-mentioned vapor-phase deposition film. The coating film is formed of a material containing a resin. In the following, an example will be described in which the gas barrier layer 11 includes a coating film formed on a vapor-phase deposition film of an inorganic oxide. The coating film protects the vapor-phase deposition film, thereby enhancing the gas barrier properties of the gas barrier layer.
[0034] The coating film is formed, for example, from a water-soluble polymer and an inorganic compound. The water-soluble polymer may be, for example, polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. From the viewpoint of improving the gas barrier properties of the gas barrier layer 11, it is preferable that the water-soluble polymer is polyvinyl alcohol (PVA).
[0035] The inorganic compound contained in the coating film is, for example, Si(OR 1 ) 4 Or, R 2 Si(OR 3 ) 3 In addition, in the chemical formula representing the silicon compound, OR 1 and OR 3 is a hydrolyzable group, R 2 is an organic functional group. The inorganic compound may include one or more silicon compounds or hydrolysates of such silicon compounds.
[0036] Si(OR 1 ) 4 For example, tetraethoxysilane (Si(OC 2 H 5 ) 4 ) (TEOS). TEOS is preferred because it is relatively stable in an aqueous solvent after hydrolysis. 2 Si(OR 3 ) 3 Contains R 2 is preferably selected from the group consisting of vinyl groups, epoxy groups, methacryloxy groups, ureido groups, and isocyanate groups.
[0037] The coating film is formed by applying a mixed solution of a solvent, a water-soluble polymer, and a silicon compound or a hydrolyzate of a silicon compound onto a deposition layer, followed by heating and drying. The solvent may be water or a mixed solvent of water and alcohol. When forming the mixed solution, first, the water-soluble polymer is dissolved in a solvent, and then the silicon compound or a hydrolyzate of a silicon compound is mixed. The mixed solution may contain additives to the extent that the coating film formed using the mixed solution does not lose its gas barrier properties. The additives may be, for example, an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity modifier, and a colorant.
[0038] When the water-soluble polymer is PVA, the ratio of the mass of PVA to the mass of the total solid content of the mixed solution is preferably 20% by mass or more and 50% by mass or less, and more preferably 25% by mass or more and 40% by mass or less. By including 20% by mass or more of PVA, the flexibility of the coating film is maintained. Therefore, the coating film is easily formed. Furthermore, by including 50% by mass or less of PVA, the gas barrier layer 11 can have sufficient barrier properties. The thickness of the coating film is selected, for example, from the range of 0.05 μm to 30 μm.
[0039] When the gas barrier layer 11 includes a vapor-phase deposited film and a coating film, the vapor-phase deposited film is located on the resin film 10, and the coating film is located on the vapor-phase deposited film in the laminate 20. This allows the coating film to be in contact with the vapor-phase deposited film.
[0040] From the viewpoint of strengthening the adhesion between the resin film 10 and the gas barrier layer 11, the surface of the resin film 10 on which the gas barrier layer 11 is formed may be subjected to a surface treatment such as a plasma treatment or a corona treatment. When the gas barrier layer 11 is formed from an inorganic oxide, an anchor coat layer may be located between the resin film 10 and the gas barrier layer 11. The surface treatment and the anchor coat layer improve the adhesion between the resin film 10 and the deposition layer after heat sterilization, and the barrier properties of the laminate 20.
[0041] In addition to the above-mentioned vapor-deposited film and coating film, or instead of at least one of the above-mentioned vapor-deposited film and coating film, the gas barrier layer 11 may include a metal foil and a layer formed from a metal nitride. When the gas barrier layer 11 includes one or more layers other than the vapor-deposited film and coating film, another layer may be located between the vapor-deposited film and the coating film. Alternatively, another layer other than the coating film may be located between the vapor-deposited film and the resin film.
[0042] The laminate 20 may include a sealing layer, an adhesive layer, a decorative layer, and an information display layer in addition to the resin film 10 and the gas barrier layer 11. The sealing layer contains a thermoplastic resin. The sealing layer is melted by heat sealing when a package is formed using the laminate 20. As a result, in two laminates 20, an end of one laminate 20 is fused to an end of the other laminate 20. Alternatively, in one laminate 20, a first portion and a second portion of the laminate 20 are fused. The adhesive layer enhances adhesion between the gas barrier layer 11 and the upper layer of the gas barrier layer 11, or between the gas barrier layer 11 and the lower layer of the gas barrier layer 11. The decorative layer displays decoration and information formed by printing.
[0043] The thickness of the laminate 20 may be selected according to various resistances required for a package formed using the laminate 20 and the processability required for the laminate 20. The thickness of the laminate 20 may be, for example, 30 μm or more and 300 μm or less.
[0044] The laminate 20 may be formed by the above-mentioned film forming method, various coating methods, a dry lamination method, an extrusion lamination method, or the like.
[0045] [Packaging] The package will now be described with reference to FIG. The packaging body 30 shown in FIG. 3 is formed from a laminate 20. The packaging body 30 defines a space capable of accommodating a packaged object inside the packaging body 30. In the example shown in FIG. 3, the packaging body 30 has a bag shape. The packaging body 30 is sealed by joining the ends over the entire circumference. In the packaging body 30, the gas barrier layer 11 is located on the inner side relative to the resin film 10. The shape and size of the packaging body 30 are not particularly limited. The shape and size of the packaging body 30 may be designed according to the shape and size of the packaged object. The packaged object may be, for example, food, medicine, cosmetics, etc.
[0046] The method of joining the ends of the laminate 20 is not particularly limited. For example, the ends of the laminate 20 may be joined using heat sealing as described above, or may be joined by other methods. In the example shown in Fig. 3, the packaging body 30 has a sealing portion 31 in which the ends of the first laminate and the second laminate are joined in two sheets of the laminate 20.
[0047] The packaging body 30 is not limited to the bag-like shape shown in FIG. 3, but may have, for example, a cylindrical shape or a bag-like shape with one cylindrical end sealed and the other cylindrical end open.
[0048] [Physical properties of resin film] The physical properties of the resin film 10 will be described with reference to FIG. Tensile tests on dumbbell-shaped test pieces are known as a method for evaluating the physical properties of resin films. The tensile test makes it possible to obtain a stress-strain curve that shows the relationship between the stress applied to the test piece and the strain of the test piece when the stress is applied. The tensile test is specified in JIS K7161-1:2014.
[0049] Fig. 4 shows an example of a stress-strain curve obtained by a tensile test on a test piece formed from the resin film 10. In the stress-strain curve shown in Fig. 4, the stress at the yield point A indicated by the arrow is the yield stress. Also, in the stress-strain curve, the breaking point B indicated by the arrow is the point at which the test piece breaks, and the stress at point B is the breaking strength.
[0050] In the stress-strain curve, the range from the point where both the stress and strain are 0 to the range where both the stress and strain are smaller than the yield point A and where the stress and strain are proportional is the range in which the resin film 10 elastically deforms. In the range of elastic deformation, the greater the slope of the stress-strain curve before bending, the harder the resin film tends to be, and the smaller the slope of the stress-strain curve, the softer the resin film tends to be.
[0051] The yield point A is the first part of the stress-strain curve where the strain increases without increasing the stress. When a stress at the yield point A, i.e., a pressure exceeding the yield stress, is applied to a resin film, the resin film undergoes plastic deformation. As a result, the deformation generated in the resin film is maintained even if the stress applied to the resin film is released.
[0052] In a stress-strain curve, the area enclosed by the curve indicates the ability of the resin film to absorb impact energy. The smaller the area enclosed by the stress-strain curve, the more brittle the resin film tends to be, i.e., the less tough it is. Conversely, the larger the area enclosed by the stress-strain curve, the less brittle the resin film tends to be, i.e., the more tough it is.
[0053] The resin film 10 satisfies the following condition 1. (Condition 1) The yield stress of the resin film 10 in the machine direction is 109 MPa or more and 117 MPa or less.
[0054] The resin film 10 tends to be harder and more brittle as the yield stress increases, whereas the resin film 10 tends to be softer and more tenacious as the yield stress decreases. When the resin film 10 is used to form the laminate described above, the resin film 10 is bonded to a gas barrier layer 11 made of an inorganic material that tends to be harder than the resin film 10. In order to prevent defects such as pinholes from occurring in the gas barrier layer 11, it is preferable that the stress acting on the gas barrier layer 11 escapes from the gas barrier layer 11 to the resin film 10. That is, it is preferable that the resin film 10 is soft and tenacious so that the stress acting on the gas barrier layer 11 is consumed inside the resin film 10. On the other hand, if the yield stress of the resin film 10 is too small, the resin film 10 is likely to undergo plastic deformation that causes defects in the gas barrier layer 11, so it is preferable that the resin film 10 has a predetermined hardness.
[0055] In this regard, the resin film 10 satisfying condition 1 is soft enough not to be too brittle, and hard enough not to cause excessive plastic deformation. Therefore, when the resin film 10 is used in the laminate 20 for forming the packaging body 30, it is possible to prevent defects from occurring in the gas barrier layer 11 formed on the resin film 10, and thus to prevent deterioration of the gas barrier properties of the laminate 20 due to the defects.
[0056] In addition, when the packaging body 30 using the laminate 20 is mass-produced, a roll-to-roll device is used, and the laminate 20 is subjected to a process for forming the packaging body 30 while the laminate 20 is being transported by the roll-to-roll device. The laminate 20 is transported by the roll-to-roll device along the flow direction of the resin film 10. At this time, the laminate 20 is transported by the roll-to-roll device in a state where it is pulled along the flow direction of the resin film 10. The resin film 10 is pulled along the flow direction with a stress that does not cause slack or bending in the laminate 20, in order to enable the transport of the laminate 20 and to prevent wrinkles from occurring in the packaging body 30 formed using the laminate 20.
[0057] Furthermore, when the package 30 containing the contents is transported, an external force that bends the package 30 is repeatedly applied and released. The direction in which such an external force due to shaking is applied and the direction in which expansion and contraction are repeatedly caused by the application and release of the external force are roughly determined based on the structure of the package 30.
[0058] In this regard, as described above, if the yield stress of the resin film 10 in the machine direction is 109 MPa or more and 117 MPa or less, it is possible to realize a yield stress large enough to suppress plastic deformation of the resin film 10 caused by the stress applied to the laminate 20 during transport of the laminate 20. Furthermore, by aligning the direction in which an external force due to shaking is applied with the machine direction of the resin film 10, it is possible to suppress plastic deformation of the resin film 10 and also suppress the associated decrease in barrier properties.
[0059] In addition to the above condition 1, the resin film 10 preferably satisfies the following condition 2. (Condition 2) In the stress-strain curve, after yielding and in the range where the strain is 0.2 or more and 0.4 or less, the slope of the stress-strain curve is included in the range of 75 or more and 117 or less.
[0060] When the resin film 10 has a yield point A, the resin film 10 has a yield point in a range where the strain is smaller than 0.1. When a stress higher than the yield stress at the yield point A is applied, the state where only the strain increases is released, and the strain increases again in accordance with the increase in stress. In a range where the strain is 0.2 or more, the increase in strain is almost proportional to the increase in stress. The greater the slope of the stress-strain curve after the yield point A, the harder the resin film 10 is, and the smaller the difference between the strain at the yield point A and the strain at the break point B tends to be. On the other hand, the smaller the slope of the stress-strain curve after the yield point A, the softer the resin film 10 is, and the larger the difference between the strain at the yield point A and the strain at the break point B tends to be. In the stress-strain curve, the resin film 10 often has a breaking point B at a point where the strain exceeds 0.4, and it is possible to grasp the tendency of the rigidity of the resin film 10 from the slope at strains of 0.4 or less.
[0061] In this regard, if a resin film 10 satisfies condition 2, when a stress greater than or equal to that causing plastic deformation is applied to the resin film 10, the strain at the breaking point B is prevented from becoming small, thereby preventing the resin film 10 from breaking and, ultimately, the occurrence of defects in the gas barrier layer 11 formed on the resin film 10.
[0062] In addition to the above condition 1, the resin film 10 preferably satisfies the following condition 3. Note that, in addition to conditions 1 and 2, the resin film 10 further preferably satisfies the following condition 3. (Condition 3) The breaking strength in the machine direction is 153 MPa or more and 183 MPa or less.
[0063] The resin film 10 tends to be harder as its breaking strength increases, and tougher as its breaking strength decreases. Therefore, if the breaking strength is too high, the stress value when the resin film 10 breaks tends to be large, while the strain that the resin film 10 can withstand tends to be small. In contrast, if the breaking strength is too low, the strain that the resin film 10 can withstand tends to be large, while the stress value when the resin film 10 breaks tends to be small.
[0064] In this regard, if the resin film 10 satisfies condition 3, it is possible to prevent either the stress or the strain that the resin film 10 can withstand without breaking from becoming excessively low, thereby making it difficult for breakage to occur in the resin film 10. As a result, it is possible to prevent defects in the deposition layer caused by breakage of the resin film 10.
[0065] The yield stress, post-yield slope, and breaking strength of the resin film 10 can be adjusted, for example, by the temperature when the resin film 10 is extruded, the temperature at which the extruded precursor of the resin film 10 is cooled, the rate at which the precursor is cooled, and the stretching ratio of the resin film 10. The yield stress, post-yield slope, and breaking strength of the resin film 10 can be adjusted, for example, by the ratio of isophthalic acid to all dicarboxylic acid units contained in the resin film 10.
[0066] For example, by increasing the temperature during extrusion molding, it is possible to increase the yield stress, the slope after yield, and the breaking strength. Also, by decreasing the temperature at which the extruded precursor of the resin film 10 is cooled, it is possible to decrease the yield stress, the slope after yield, and the breaking strength. Also, by increasing the rate at which the precursor is cooled, it is possible to decrease the yield stress, the slope after yield, and the breaking strength. Also, by increasing the ratio at which the resin film 10 is stretched, it is possible to decrease the yield stress, the slope after yield, and the breaking strength. Also, by increasing the ratio of isophthalic acid to all dicarboxylic acid units contained in the resin film 10, it is possible to decrease the yield stress, the slope after yield, and the breaking strength.
[0067] [Example] With reference to FIG. 5 and Tables 1 to 4, examples and comparative examples will be described. [Example 1] Three resin layers were laminated by co-extrusion to form a resin film 10 of Example 1 having a thickness of 12 μm. At this time, three resin layers having the same composition were formed from recycled PET regenerated by mechanical recycling and virgin PET. In the resin film 10 of Example 1, the mass of the recycled PET was set to 80% of the total mass of the resin film, and the mass of the virgin PET was set to 20% of the total mass of the resin film.
[0068] [Example 2] Three resin layers were laminated so that the second resin layer was sandwiched between two first resin layers to form a resin film 10 of Example 2 having a thickness of 12 μm. In this case, the first resin layer was formed from virgin PET. In addition, the second resin layer was formed from recycled PET regenerated by chemical recycling. In the resin film of Example 2, the mass of the recycled PET was set to 70% of the total mass of the resin film 10.
[0069] [Example 3] Three resin layers were laminated so that the second resin layer was sandwiched between two first resin layers to form a resin film 10 of Example 3 having a thickness of 12 μm. At this time, the first resin layer was formed from recycled PET recycled by chemical recycling. In addition, the recycled PET recycled by chemical recycling was mixed with the recycled PET recycled by mechanical recycling to form the second resin layer. In the second resin layer, the mass of the recycled PET recycled by mechanical recycling was set to 80% of the total mass of the second resin layer, and the mass of the recycled PET recycled by chemical recycling was set to 20% of the total mass of the second resin layer. In the resin film of Example 3, the mass of the recycled PET was set to 100% of the total mass of the resin film 10.
[0070] [Comparative Example 1] A single resin layer was formed using virgin PET to obtain a resin film 10 of Comparative Example 1 having a thickness of 12 μm. In the resin film 10 of Comparative Example 1, the mass of the recycled PET was set to 0% relative to the total mass of the resin film.
[0071] [Example 4] A deposition layer having a thickness of 10 nm, which was formed from aluminum oxide using a vacuum deposition method, was laminated on the resin film 10 of Example 1. Furthermore, a coating film having a thickness of 0.3 μm was formed on the deposition layer using gravure coating. At this time, a first solution was prepared by adding hydrochloric acid to tetraethoxysilane and stirring for 30 minutes to hydrolyze tetraethoxysilane, and a second solution was prepared by dissolving polyvinyl alcohol in a solution obtained by mixing water and isopropyl alcohol. Then, 60 parts by mass of the first solution and 40 parts by mass of the second solution were mixed to prepare a coating agent. After applying the coating agent on the deposition layer using a bar coater, the coating film was formed by drying the coating agent at 120° C. for 1 minute using a dryer. As a result, a laminate of Example 4 including the resin film 10 and the gas barrier layer 11 including the deposition layer and the coating film was obtained.
[0072] [Comparative Example 2] A laminate of Comparative Example 2 was obtained using the same materials and method as in Example 1, except that in Example 2, the resin film 10 of Example 1 was changed to the resin film of Comparative Example 1. This resulted in a laminate of Comparative Example 2 including the resin film of Comparative Example 1 and a gas barrier layer 11 including a resin layer and a coating film.
[0073] [Evaluation method] [Stress-strain curve] Two or three test pieces were cut out from the resin films of Examples 1 to 3 and Comparative Example 1. At this time, using a dumbbell cutter (Dumbbell Co., Ltd., SDK-600) conforming to JIS Z 1702-1994, each test piece was cut out so as to have a shape extending along the flow direction. That is, the test pieces were cut out from the resin film so that the tensile direction of each test piece coincided with the flow direction of the resin film. Then, two benchmark lines for measuring elongation were marked on each test piece.
[0074] Using a small tabletop testing machine (EZ-LX, manufactured by Shimadzu Corporation), the test pieces were Tensile tests were performed using a method conforming to K7161-1:2014. At this time, each test piece was fixed to a small benchtop testing machine, and the gauge line was clamped with an extensometer. The test speed was set to 300 mm / min. Based on the results of the tensile tests on one test piece for each of Examples 1 to 3 and Comparative Example 1, a stress-strain curve was created. From the stress-strain curve, the yield stress, the breaking strength, and the slope after yielding and in the range where the strain was 0.2 to 0.4 were obtained.
[0075] [Gas barrier properties] Two test pieces were prepared from each of the laminate of Example 4 and the laminate of Comparative Example 2, and the gas barrier properties were evaluated before and after the Gelbo flex test. The Gelbo flex test, the oxygen permeability measurement, and the water vapor permeability measurement were performed under the conditions described below.
[0076] [Gelboflex test] A Gelbo Flex test was performed on each test piece using a flexibility evaluation device (Gelbo Flex Tester, manufactured by Tester Sangyo Co., Ltd.). At this time, each test piece was attached to the fixed head of the flexibility evaluation device so as to have a cylindrical shape. In detail, both ends of each test piece were held by the fixed head, and the initial gripping distance was set to 175 mm. Then, the stroke was set to 87.5 mm, the twist was set to 440°, and each test piece was twisted and released from the twist, and the reciprocating motion was performed 10 times at a speed of 40 times / min.
[0077] [Oxygen permeability] The oxygen permeability of each test piece was measured before and after the Gelbo Flex test using an oxygen permeability measuring device (OX-TRAN 2 / 20, manufactured by Mocon). The method used was in accordance with JIS K 7126-2:2006 and ASTM D3985-81. The temperature was set to 30°C and the relative humidity was set to 70%. The unit of the measured oxygen permeability is [cm 3 (STP) / m 2 ·day·MPa].
[0078] [Water vapor permeability] The water vapor permeability of each test piece was measured before and after the Gelbo Flex test using a water vapor permeability measuring device (Mocon, PERMATRAN-W 3 / 31). The measurements were performed at a temperature of 40°C and a relative humidity of 90%. The measurement method used was in accordance with JIS K 7129-2:2019 and ASTM F1249-90. The unit of the measured water vapor permeability is [g(STP) / m 2 -day].
[0079] [Evaluation Results] The evaluation results based on the above-mentioned evaluation method will be described with reference to FIG. 5 and Tables 1 to 4. The stress-strain curves obtained for the resin films of Examples 1 to 3 and Comparative Example 1 were as shown in FIG. 5. FIG. 5 shows an example of the stress-strain curve obtained for each resin film. The yield stress was as shown in Table 1 below, the slope after yield was as shown in Table 2 below, and the breaking strength was as shown in Table 3 below. The oxygen permeability and water vapor permeability of the laminate of Example 4 and the laminate of Comparative Example 2 were as shown in Table 4 below.
[0080] [Table 1]
[0081] As shown in Table 1, in the test examples of Example 1 to Example 3, it was confirmed that the average value of the yield stress was in the range of 100 Pa or more and 116 Pa or less. In addition, in each test example, it was confirmed that the value of the yield stress was in the range of 109 MPa or more and 117 MPa or less. In contrast, in the test example of Comparative Example 1, the average value of the yield stress was 124.8 MPa, and the value of the yield stress in each test example was approximately 125 MPa. Thus, it was confirmed that the value of the yield stress in each test example of Example 1 to Example 3 was smaller than the value of the yield stress in Comparative Example 1.
[0082] [Table 2]
[0083] As shown in Table 2, in the test examples of Example 1 to Example 3, it was confirmed that the average value of the slope after yield was within the range of 77 to 111. In addition, in each test example, it was confirmed that the value of the slope after yield was within the range of 75 to 117. In contrast, in the test example of Comparative Example 1, the average value of the slope after yield was 172.4, and in the two test examples, the slope after yield was 172.1 and 172.6. Thus, it was confirmed that the slope after yield in each test example of Example 1 to Example 3 was smaller than the slope after yield in Comparative Example 1.
[0084] [Table 3]
[0085] As shown in Table 3, in the test examples of Example 1 to Example 3, it was confirmed that the average value of the breaking strength was in the range of 159 MPa or more and 177 MPa or less. In addition, in each test example, it was confirmed that the value of the breaking strength was in the range of 153 MPa or more and 183 MPa or less. In contrast, in the test example of Comparative Example 1, the average value of the breaking strength was 202.7, and in the two test examples, the breaking strengths were 195.3 and 210.1. Thus, it was confirmed that the breaking strengths in each test example of Example 1 to Example 3 were smaller than the breaking strength in Comparative Example 1.
[0086] [Table 4]
[0087] As shown in Table 4, it was confirmed that the average value of oxygen permeability after the Gelbo flex test in Example 4 was smaller than the average value after the Gelbo flex test in Comparative Example 2. It was also confirmed that the amount of change before and after the Gelbo flex test in Example 4 was smaller than the amount of change in Comparative Example 2. It was also confirmed that the average value of water vapor permeability after the Gelbo flex test in Example 4 was smaller than the average value after the Gelbo flex test in Comparative Example 2. It was also confirmed that the amount of change before and after the Gelbo flex test in Example 4 was smaller than the amount of change in Comparative Example 2.
[0088] Thus, the laminate of Example 1 has increased pinhole resistance caused by vibration during transportation, etc., as simulated by the Gelbo Flex test, and this can be said to suppress a decrease in oxygen permeability and water vapor permeability, i.e., a decrease in gas barrier properties.
[0089] As described above, according to one embodiment of the resin film, the laminate, and the packaging body, the following effects can be obtained. (1) The resin film 10 can be soft enough not to be too brittle, and hard enough not to cause excessive plastic deformation. Therefore, when the resin film 10 is used in the laminate 20 for forming the packaging body 30, it is possible to suppress a decrease in the gas barrier properties of the laminate 20 caused by defects occurring in the vapor deposition layer formed on the resin film 10.
[0090] (2) When a stress sufficient to cause plastic deformation is applied to the resin film 10, the strain at the breaking point B is prevented from becoming small, thereby preventing the resin film 10 from breaking and, ultimately, preventing defects from occurring in the vapor deposition layer formed on the resin film 10.
[0091] (3) It prevents either the stress or the strain that the resin film 10 can withstand without breaking from becoming excessively low, thereby preventing breakage of the resin film 10. As a result, it is possible to prevent defects in the deposition layer caused by breakage of the resin film 10.
[0092] (4) According to the laminate 20 including the resin film 10 and the gas barrier layer 11, even when a stress that distorts the laminate 20 is applied to the laminate 20, deterioration in the gas barrier properties of the laminate 20 is suppressed. This enhances the suitability of the laminate 20 for use as a packaging material.
[0093] (5) The packaging body 30 formed from the laminate 20 prevents deterioration of the gas barrier properties of the packaging body 30 caused by vibrations applied to the packaging body 30 during transportation of the product. This prevents deterioration in the quality of the object packaged in the packaging body 30. [Explanation of symbols]
[0094] 10...Resin film 11...Gas barrier layer 20...Laminate 30...packaging
Claims
1. A resin film containing polyethylene terephthalate, the resin film being used to produce a packaging body from a laminate including the resin film and a gas barrier layer, The resin film contains recycled polyethylene terephthalate as the polyethylene terephthalate, The recycled polyethylene terephthalate is at least one of mechanically recycled polyethylene terephthalate and chemically recycled polyethylene terephthalate, The resin film has a yield stress in the machine direction according to JIS K7161-1:2014 of 109 MPa or more and 117 MPa or less, In the stress-strain curve obtained in the machine direction, the slope of the stress-strain curve after yielding and in the range where the strain is 0.2 or more and 0.4 or less is 75 or more and 117 or less. Resin film.
2. The breaking strength in the machine direction is 153 MPa or more and 183 MPa or less. The resin film according to claim 1 .
3. The proportion of the recycled polyethylene terephthalate to the total mass of the resin film is 70% or more. The resin film according to claim 1 or 2.
4. The recycled polyethylene terephthalate contains terephthalic acid and isophthalic acid in the dicarboxylic acid units in the repeating units. The resin film according to claim 1 .
5. In the resin film, the ratio of isophthalic acid to all dicarboxylic units is 0.5 mol % or more and 5 mol % or less. The resin film according to claim 4.
6. The resin film according to any one of claims 1 to 5, A gas barrier layer is provided. Laminate.
7. The gas barrier layer comprises a vapor deposition layer, The vapor-deposited layer is an inorganic oxide vapor-deposited layer or a metal vapor-deposited layer, The inorganic oxide vapor deposition layer is formed from any one of oxides of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, and yttrium; The metal deposition layer is formed from any one of aluminum, magnesium, tin, sodium, titanium, lead, zirconium, yttrium, gold, and chromium. The laminate according to claim 6.
8. The gas barrier layer is a first barrier layer comprising at least one of aluminum oxide, silicon oxide, and aluminum; and a second barrier layer comprising a polymeric material. The laminate according to claim 6.
9. The first barrier layer and the second barrier layer are in contact with each other. The laminate according to claim 8.
10. The second barrier layer is Si(OR 1 ) 4 , or R 2 Si(OR 3 ) 3 (OR 1 and OR 3 is a hydrolyzable group, R 2 is an organic functional group), or one or more hydrolyzates of a silicon compound, and a water-soluble polymer having a hydroxyl group. The laminate according to claim 8 or 9.
11. The thickness of the laminate is 30 μm or more and 300 μm or less. The resin film according to any one of claims 6 to 10.
12. The resin film according to any one of claims 1 to 5, A gas barrier layer is provided. packaging.
Citation Information
Patent Citations
Biaxially-oriented polyester film obtained by using pet bottle-recycled raw material
JP2014065282A
Exterior material for vacuum heat insulation material and vacuum heat insulation material
JP2020032596A
Oxygen plasma treated resin film, gas barrier vapor deposition film and gas barrier laminate using the gas barrier vapor deposition film, gas barrier packaging material, gas barrier package, gas barrier packaging bag and manufacturing method of these
JP2020070429A
Layered film
WO2015146496A1
Laminated multilayer body and packing bag made of the same
JP2019081607A